2006
DOI: 10.1016/j.cellimm.2006.05.007
|View full text |Cite
|
Sign up to set email alerts
|

DNase II deficiency impairs innate immune function in Drosophila

Abstract: DNase II enzymes are highly conserved proteins that are required for the degradation of DNA within phagolysosomes. Engulfment of apoptotic cells and/or bacteria by phagocytic cells requires the function of DNase II to completely destroy ingested DNA. Mutation of the dnase II gene results in an increase of undegraded apoptotic DNA within phagocytic cells in mice and nematodes. Additionally, reduction of DNase II enzymatic activity in Drosophila melanogaster has been shown to lead to increased accumulation of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…The present study using Drosophila third instar larvae supports the scenario that Toll signaling is a key mechanism in the host defense system that responds to endogenous inflammatory factors, consistent with the dedicated role of Toll-like receptors in vertebrate "danger" sensing (1,47,48). A number of previous studies that focused on nonmicrobial signal-activated host defense in Drosophila showed that the Imd/Relish cascade is activated by endogenous inflammatory agents, such as undigested DNA (49,50) and the neuro-peptide bursicon (51), as well as undefined humoral factors released from the intestine after tissue damage (52). The observation of different signaling pathways that are activated in response to various forms of stress, and in the dronc mutant, indicate that specific detection mechanisms are used to discriminate among various forms of threat.…”
Section: Discussionsupporting
confidence: 88%
“…The present study using Drosophila third instar larvae supports the scenario that Toll signaling is a key mechanism in the host defense system that responds to endogenous inflammatory factors, consistent with the dedicated role of Toll-like receptors in vertebrate "danger" sensing (1,47,48). A number of previous studies that focused on nonmicrobial signal-activated host defense in Drosophila showed that the Imd/Relish cascade is activated by endogenous inflammatory agents, such as undigested DNA (49,50) and the neuro-peptide bursicon (51), as well as undefined humoral factors released from the intestine after tissue damage (52). The observation of different signaling pathways that are activated in response to various forms of stress, and in the dronc mutant, indicate that specific detection mechanisms are used to discriminate among various forms of threat.…”
Section: Discussionsupporting
confidence: 88%
“…A role for STING has not been investigated in the DNase II mutant fly, but we showed that it is unlikely to play a role in DNA-induced cell death. However, given the likely escape of undigested DNA into the cytosol of DNase II mutant cells, the cell death pathway we have described is consistent with the documented low level of haemocytes in the DNase II mutant flies [33]. …”
Section: Discussionsupporting
confidence: 83%
“…DNA within apoptotic cells is cut into nucleosomal units by caspase-activated DNase, and further DNase II-dependent degradation occurs following uptake into a macrophage phagolysosome [30,31]. A mutation in the Drosophila DNase II orthologue that leads to diminished enzyme activity results in accumulation of DNA in apoptotic cells in the ovary, increased susceptibility to bacterial infections, a reduced number of haemocytes, and elevated levels of the antimicrobial peptides diptericin and attacin A [32,33]. The induction of antimicrobial peptides was further increased in DNase II mutant flies without functional Drosophila caspase-activated DNase [32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the nematode support this hypothesis: mutations in NUC-1 mimic mutations in the engulfment machinery, resulting in increased cell survival (Wu et al, 2000). Interestingly, Drosophila lacking DNase II also show decreased ability to phagocytose bacteria, providing further support for the idea that signaling from the lysosome to the phagosome is important for efficient phagocytosis (Seong et al, 2006).…”
Section: Dna Degradation Following Phagocytosismentioning
confidence: 62%